Pomalidomide and Dexamethasone Are Effective in Relapsed or Refractory Multiple Myeloma in a Real-Life Setting: A Multicenter Retrospective Study in Taiwan - Hung, Yu-Chin; Gau, Jyh-Pyng; Huang, Shang-Yi; Ko, Bor-Sheng; Teng, Chieh-Lin Jerry (Frontiers in Oncology, 2021)
Background: The therapeutic options of relapsed or refractory multiple myeloma (RRMM) remain a challenge. The MM-003 trial demonstrated that RRMM patients treated with pomalidomide and dexamethasone (Pom/Dex) have better progression-free survival (PFS) than those treated with high-dose dexamethasone alone. However, the real-world effectiveness of Pom/Dex in these patients in Taiwan remains unclear. Methods: This multicenter, registry-based study retrospectively reviewed the medical records of 49 consecutive patients undergoing Pom/Dex treatment for RRMM. We investigated the overall response rate (ORR) and PFS in these patients. The patients were stratified into two groups: those who received two (n=33) and those who received more than two (n=16) prior lines of treatment according to the numbers of regimens before Pom/Dex therapy. The differences in ORR and PFS between these two groups were further analyzed. We also analyzed factors attributed to disease progression. Results: The ORR was 47.7%, and the median PFS was 4.0 months (range, 0.1−21.1). Patients who received two prior lines of treatment had a higher ORR than those who received more than two prior lines of treatment (55.2% vs. 33.3%; p=0.045). The median PFS of these groups was 4.8 and 3.9 months, respectively (p=0.805). Primary lenalidomide refractoriness reduced the risk of myeloma progression following Pom/Dex treatment (hazard ratio, 0.14; p=0.001). Conclusions: The median PFS following Pom/Dex treatment in Taiwanese RRMM patients in a real-world setting was similar to that reported by the MM-003 trial. Primary lenalidomide refractoriness should not be an obstacle for Pom/Dex treatment in RRMM.